Virulent Properties of Russian Bovine Viral Diarrhea Virus Strains in Experimentally Infected Calves. (14th April 2016) - Glotov, Alexander G.; Glotova, Tatyana I.; Koteneva, Svetlana V.; Semenova, Olga V.; Sergeev, Alexander A.; Titova, Ksenya A.; Morozova, Anastasia A.; Sergeev, Artemiy A.
Abstract : The results of experimental study of three noncytopathic and two cytopathic bovine viral diarrhea virus (BVDV) strains isolated from cattle in the Siberian region and belonging to the type 1 (subtypes 1a, 1b, and 1d) have been presented. All investigated strains caused the development of infectious process in the seronegative 4–6-month-old calves after aerosol challenge with the dose of 6 log10 TCID50 . The greatest virulence had noncytopathic strain and cytopathic strain related to the subtypes 1d and 1b, respectively. All strains in infected calves caused some signs of moderate acute respiratory disease and diarrhea: depression 3–5 days postinfection (p.i.), refusal to food, severe hyperthermia to 41.9°С, serous exudate discharges from the nasal cavity and eyes, transient diarrhea with blood, leukopenia (up to 2700 cells/mm 3 ), and macroscopic changes in the respiratory organs and intestine. The infected animals recovered from 12 to 15 days p.i. and in 90% cases formed humoral immune response 25 days p.i. (antibody titers to BVDV: 1 : 4–1 : 16). Our results confirmed the presence of virulent BVDV1 strains and showed the need for researches on the molecular epidemiology of the disease, development of more effective diagnostic systems, and optimization of control programs with use of vaccines.